Art Education and Disability Studies - Derby, John (Disability Studies Quarterly, 2012)
This article explores the field of Art Education as a valuable contributor to Disability Studies. Art Education has longstanding ties to disability research and pedagogy, and recent advancements in Art Education as well as Disability Studies closely align the two fields. Their mutual investment in visual culture studies engenders the possibility for a transdisciplinary space in which disability can be explored in new pedagogical ways to yield unique artifacts. Through several Art Education perspectives, I propose strategies for interjecting meaningful art activities into post-secondary, humanities-based Disability Studies curricula. Keywords art, Art Education, visual culture, disability, Disability Studies, transdisciplinary